Hysterosalpingographic findings in infertility — what has changed over the years? - Omidiji, Olubukola AT (Afr Health Sci, 2019)
BACKGROUND: Prior studies on Hysterosalpingography (HSG) have shown that pelvic inflammatory disease (PID) related tubal adhesions accounted for 30 – 50% of female infertility, with as high as 80% reported in some studies. With improved access to contraceptives, antibiotics and promotion of safe practices, the abnormal findings in HSG may have reduced or altered. OBJECTIVE: To document the imaging findings in the HSG of participants and to compare current findings with prior studies done nationally and internationally. METHOD: A retrospective evaluation of 974 HSGs done at the tertiary diagnostic center over a 7-year period was conducted and analyzed using diagnostic accuracy tables. RESULTS: Tubal pathologies were the most common abnormality in this study, (35.1% of the cases), comprising tubal blockage and hydrosalpinges; followed by uterine masses seen in 223 (22.9%) of the clients. Tubal occlusion was higher in clients with multiple abnormal findings; while normal sized and large uterine cavities had a higher percentage of bilateral tubal patency. CONCLUSION: Tubal factors remain the most common abnormality seen in the HSGs of infertile women in this study, though with lower prevalence compared with prior older studies. Forty seven (47%) of the cases of female factor infertility had normal HSGs with bilateral tubal patency.